Sympathetic nervous system hyperactivity-induced oxidative stress promoting endothelial dysfunction is dependent on the NADPH oxidases/SGLT2 crosstalk: potential role in cardiogenic shock. (3rd October 2022) - Kerth, S; Petry, A; Kracun, D; Morel, O; Schini-Kerth, V B; Goerlach, A
Abstract: Background: Hyperactivity of the sympathetic nervous system (SNS) promotes cardiac dysfunction, that can contribute to heart failure and even cardiogenic shock. Endothelial dysfunction associated with increased formation of reactive oxygen species (ROS) has been suggested to promote cardiac dysfunction and heart failure. Our previous results showed that SGLT2 and ROS derived from endothelial NADPH oxidases contribute to cardiac dysfunction. Purpose: Therefore, this study examined whether cardiogenic shock and hyperactivation of the SNS involve NADPH oxidases and SGLT2 in the development of endothelial dysfunction using in vitro and in vivo approaches. Methods: Peripheral blood from patients with cardiogenic shock and healthy controls was drawn by vein puncture into tubes containing sodium citrate. Cultured human microvascular endothelial cells (HMEC-1) were stimulated with either 100 nM of the β-adrenergic agonist isoproterenol or with heparinized (10 U/ml) patient plasma. Male wild-type mice and mice lacking the NADPH oxidase subunit p22phox in the endothelium (p22phox ecKO, 11-week-old) were treated with isoproterenol (100 mg/kg) for five consecutive days and sacrificed at day 14. ROS levels were assessed by dihydroethidium fluorescence, and the expression levels of target genes and proteins by RT-qPCR and Western blot, respectively. siRNA approaches were used to down-regulate the NADPH oxidase subunit p22phox or SGLT2. Results: Exposure of HMEC-1 to either plasma from patients suffering from cardiogenic shock or isoproterenol stimulated the formation of ROS. ROS levels were reduced by N-acetylcysteine (an antioxidant) and silencing of p22phox, by empagliflozin (a selective SGLT2 inhibitor) and silencing of SGLT2 as well as by metoprolol (a beta1 adrenergic receptor antagonist) and ICI-118, 551 (a beta2 adrenergic receptor antagonist). Cardiogenic shock patient plasma and isoproterenol upregulated the NADPH oxidase subunits p22phox and Nox4 as well as SGLT2. These responses were prevented by silencing of either p22phox or SGLT2, and by empagliflozin. In addition to improved cardiac function and blunted SGLT2 expression, p22phox ecKO mice were protected against isoproterenol-induced endothelial dysfunction and senescence, characterized by upregulation of eNOS, nitrotyrosine, VCAM-1 and p16 in the left ventricle. Conclusion: SNS hyperactivity and cardiogenic shock-derived patient plasma cause a feed forward loop between NADPH oxidases and SGLT2, promoting pro-oxidant responses and endothelial dysfunction via activation of both beta1 and beta2 adrenergic receptors. The NADPH oxidase/SGLT2 crosstalk also contributes to SNS hyperactivity-induced senescence, cardiac and endothelial dysfunction. Thus, the endothelial NADPH oxidases/SGLT2 crosstalk appears to have a major role in cardiac diseases associated with SNS hyperactivity such as cardiogenic shock. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Deutsches Herzzentrum München